The Effect Of Discovery Learning Combined With Video Scribe Animation Media On Learning Motivation Viewed From Student Academic Ability - Septi Krisyanti; Slamet Santosa; Dewi Puspitasari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
Learning motivation is an important element of learning to achieve learning outcomes. Learning model accompanied by innovative learning media as an effort to increase student motivation. This research aims to (1) know the effect of discovery learning combined with videoscribe animation media on students learning motivation, (2) know the effect of academic abilities on students learning motivation, and (3) know the interactions between discovery learning, videoscribe animation media, and academic abilities towards students learning motivation. This research was a quasi-experiment. The study population was all XI MIPA grade students of SMAN 8 Surakarta. The research subject was taken using simple random sampling. Data collection techniques use documentation, questionnaires, and observation. The data analysis using Two Way Anova test with SPSS 24.The results obtained are sig.(A) of 0,005; sig.(B) of 0,447; and sig.(AB) of 0,461. Sig.<0,05. The conclusion of the hypothesis test results shows that (1) H0(learning model) is significantly rejected which means there is a significant effect of discovery learning combined with animation media video scribe to students' motivation, 2) H0(academic ability) accepted which means there is no effect of low, medium, and high academic ability on student motivation, and 3) H0(learning model* academic ability) is accepted which means there is no interaction between learning models and academic ability on students' motivation.The conclusion of this research showed that (1) discovery learning combined with video scribe animation media influences students learning motivation, (2) academic ability no influences students learning motivation, and (3) there is no interaction between discovery learning, video scribe animation media, and academic abilities on students learning motivation